(untitled) (Ustozlar uchun, 2026)
This article explores the concept of creating an e-portfolio as a modern educational and professional tool. It analyzes the importance of e-portfolios in learning, assessment, and career development. Special attention is given to the structure, types, and practical applications of e-portfolios. The study highlights the benefits, challenges, and strategies for effective e-portfolio creation.